Amino acids as indicators to elucidate organic matter degradation profile in the Cochin estuarine sediments, Southwest coast of India. (February 2018) - Salas, P.M.; Sujatha, C.H.; Ratheesh Kumar, C.S.; Cheriyan, Eldhose
Abstract: Surface sediments from three zones (fresh water, estuarine, and riverine/industrial zones) of the Cochin estuary, Southwest coast of India, were seasonally analyzed to understand the nature and degradation status of organic matter. Amino acid-based indices such as total hydrolyzable amino acids (THAAs), percentage contributions of amino acid carbon to total organic carbon (THAA-C%) and those of amino acid nitrogen to total nitrogen (THAA-N%), and degradation index (DI) were calculated. Elevated levels of amino acids in the sediments of the estuary were attributed to river runoff, autochthonous production, allochthonous inputs, and industrial and domestic effluent discharges. Higher levels of THAA-C%, THAA-N%, THAA, and positive DI found in most of the stations suggest the fresh deposition of organic matter. Multivariate statistical analyses revealed that the dispersal pattern of amino acids depends on the sediment texture, organic matter, redox state, and microbial processes in the study region. Highlights: Degradation status of organic matter is evaluated through amino acid indices in the Cochin Estuary. Amino acid concentrations are predominantly controlled by microbial processes. Degradation index and total hydrolyzable amino acids indicated freshly derived organic matter.